STUDI PEMANFAATAN LIMBAH BIOMASSA PERTANIAN SEBAGAI BIOADSORBEN UNTUK MENYERAP ION Cr - Arif Setiawan, Andi (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2013)
This study aims to assess the ability of agricultural biomass waste as material adsorbent in the form of : rice husk, sawdust and peanut skins in total Cr ions adsorb. Ion concentration of 300 ppm Cr is used as much as 100 ml, with a contact time of 30, 60, 90, 120 and 150 minutes. The results showed the presence of intereaksi between bioadsorben with real-time contact with the Cr ions absorb 11.235 F count> F table 2.27 5%. Rice husk has the largest absorption than powders and porters gergai peanuts, respectively absorbance at 150 minutes contact time is 4.00 mg / g, 6.534 mg / g and 5.452 mg / g. Key words : ion Cr, waste agricultur biomass, rice husk, sawdust, peanut shell